Chronische Schmerzstörung mit somatischen und psychischen Faktoren (F45.41): Prüfkriterien zur Operationalisierung der ICD-10-GM-Diagnose - Arnold, Bernhard; Schiltenwolf, Marcus (Der Schmerz, 2017)
In 2009 the diagnosis chronic pain disorder with somatic and psychological factors (F45.41) was integrated into the German version of the International Classification of Diseases, version 10 (ICD-10-GM). In 2010 Paul Nilges and Winfried Rief published operationalization criteria for this diagnosis. In the present publication the ad hoc commission on multimodal interdisciplinary pain therapy of the German Pain Society now presents a formula for a clear validation of these operationalization criteria of the ICD code F45.41.